1988
DOI: 10.1136/bmj.297.6650.729
|View full text |Cite
|
Sign up to set email alerts
|

How many beds? Helping consultants to estimate their requirements.

Abstract: Two studies were carried out in different districts with clinicians who were concerned about the proposed numbers of beds to be provided based on regional targets and assessments. It was found that summary statistics can obscure wide variations over time in the demand for services. Providing beds according to average demand can therefore create a shortage of beds for a large part of the year. It is argued that the norms and targets set by regions should be seen as a starting point for negotiations rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The exception to this will be in the case of a stable system. While Millard and his colleagues have stated that the system used for the development of the model was stable [23,36], evidence exists that hospital systems are generally unstable and are challenged by differing workload demands at different times of the week or year [34,35]. Millard and his colleagues also acknowledged it in later work [33,37].…”
Section: Compartmental Modelsmentioning
confidence: 98%
See 1 more Smart Citation
“…The exception to this will be in the case of a stable system. While Millard and his colleagues have stated that the system used for the development of the model was stable [23,36], evidence exists that hospital systems are generally unstable and are challenged by differing workload demands at different times of the week or year [34,35]. Millard and his colleagues also acknowledged it in later work [33,37].…”
Section: Compartmental Modelsmentioning
confidence: 98%
“…St George [34] and MacStravic [35] have reported that an annual average model of acute hospital services will be insufficient to enable bed planning, as the variation within the data will not be detected. Variation in the data stems from day of week and seasonal differences in workloads as well as other factors.…”
Section: Compartmental Modelsmentioning
confidence: 99%